Links between Vitamin D deficiency and diabetes-associated macrovasculopathy - Rahman, Sayeeda; Majumder, Md Anwarul Azim (South East Asia Journal of Public Health, 2016)
Abstract not available South East Asia Journal of Public Health Vol.5(2) 2015: 4-6